DESKRIPSI PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER ( NHT ) PADA PEMBELAJARAN MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Fivtia Neri Yusra; KMA Fauzi; Andayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was executed with the primary objective of thoroughly investigating the application and confirmed efficacy of the Numbered Head Together (NHT) Cooperative Model.The central focus of this research was its implementation within the context of Mathematics Instruction for fifth-grade students in elementary schools. The design and execution of this model specifically targeted three crucial pedagogical dimensions: promoting enhanced collaborative activity among students, cultivating a stronger sense of individual accountability, and solidifying students' conceptual understanding of the subject matter. Technically, the NHT procedure involved several core sequential stages:1)Numbering:Assigning a distinct identification number to each student within their respective teams.2) Discussion:Posing a question that necessitates a compulsory group discussion to collectively find a solution.3)Idea Consolidation: The moment when team members synchronize their thoughts and arrive at a consensus for the final answer.4) Random Call:The instructor randomly selects a number to designate which student will represent the group's response—a mechanism proven to effectively ensure the preparedness of every team member.Furthermore, the model demonstrated an ability to increase student participation across the board and, critically, resulted in a significant improvement in their Mathematics learning achievements, particularly concerning problem-solving competency.Based on these compelling results, it is concluded that the NHT Cooperative Model is exceptionally relevant and highly effective as a strategic instructional choice for Mathematics education at the primary school level. Consequently, it is strongly recommended that educators consider and adopt NHT as a viable pedagogical alternative for designing learning activities that actively demand both participatory engagement and robust teamwork from their students.